Pubertal Development, Spare Time Activities, and Adolescent Delinquency: Testing the Contextual Amplification Hypothesis - Kretschmer, Tina; Oliver, Bonamy R.; Maughan, Barbara (Journal of Youth and Adolescence, 2014)
Extensive evidence supports associations between early pubertal timing and adolescent externalizing behavior, but how and under which conditions they are linked is not fully understood. In addition, pubertal development is also characterized by variations in the relative speed at which individuals mature, but studies linking pubertal 'tempo' and outcomes are scarce. This study examined the mediating and moderating roles of spare time activities in associations between pubertal development and later delinquency, using data from a large (4,327 girls, 4,250 boys) longitudinal UK cohort (Avon Longitudinal Study of Parents and Children). Self-reports of Tanner stage were available from ages 9 to 14, spare time activities at age 12 and delinquency at age 15. Pubertal development was examined using latent growth models. Spare time activities were categorized using factor analyses, yielding four types (hanging out at home, hanging out outside, consumerist behavior, and sports/games), which were examined as mediators and moderators. Earlier and faster maturation predicted delinquency in boys and girls. Spare time activities partially mediated these links such that early maturing girls more often engaged in hanging out outside, which placed them at greater risk for delinquency. In addition, compared to their later and slower maturing counterparts, boys who matured earlier and faster were less likely to engage in sports/games, a spare time activity type that is linked to lower delinquency risk. No moderation effects were found. The findings extend previous research on outcomes of early maturation and show how spare time activities act as proxies between pubertal development and delinquency. © 2013 Springer Science+Business Media New York.
CRIS-Team Scopus Importer:2025-03-19
Keywords: ALSPAC; Delinquency; Latent growth model; Pubertal development